Impact of Angiotensin II Type 1 Receptor Gene Polymorphism on Insulin Resistance in Polycystic Ovary Syndrome - El-Mesallamy, H.; El-Refaie, T.; El-Razek, R. A. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Insulin resistance is allegedly a target pathophysiological mechanism in the pathogenesis of polycystic ovary syndrome. Moreover, this metabolic alteration is possibly genetically determined. In view of the recent evidence implicating genetic variants of the renin-angiotensin system as candidates in several metabolic disorders, we investigated the allele and genotype frequencies of the A1166 C polymorphism of the angiotensin II type 1 receptor in relation with various metabolic and biochemical parameters in affected females trying to asses its role in the pathogenesis of this syndrome. The study was conducted on 83 females of which 39 females served as the control group. The participants were matched for age, body mass index and degree of obesity. For all subjects biochemical parameters were assayed including soluble CD40 ligand together with fasting glucose and insulin which were used for calculation of insulin resistance indices, Genotyping performed using real time polymerase chain reaction revealed that the C allele frequency and the AC genotype were less frequently observed in patients compared to controls, however this difference was not statistically significant (p=0.146). Lack of the C allele was associated with adverse metabolic parameters including higher rate of insulin resistance as well as solubes CD40 ligand in the patients group. Results of the current study support a causative role for the A1166 C polymorphism of the angiotensin II type 1 gene polymorphism in the pathogenesis or phenotypic expression of polycystic ovary syndrome.
Keywords: A1166C angiotensin II type 1 receptor gene polymorphism; real time polymerase chain reaction; insulin resistance indices; soluble CD40L